House prices and consumption inequality - Ben Etheridge (Institute for Fiscal Studies (IFS), 2019)
I characterize how house price shocks affect consumption inequality using a life-cycle model of housing and non-housing consumption with incomplete markets. I derive analytical expressions for the dynamics of inequalities and use these to analyze large house prices swings seen in the UK. I show that movements in consumption inequality were large, that they correspond with the theoretical predictions qualitatively, and that the model explains a large fraction of the movements quantitatively. I demonstrate the accuracy of this analysis using an extended model's full non-linear solution. Finally, accounting for house price shocks alters estimates of labour-income risks using cross-sectional data.
Keywords: D31; D91; E21; 330; Consumption inequality; Wealth effect; Collateral effect; Housing